Features of growth and development Of tea selection forms in adygea - L. V. Vavilova; B. V. Korzun (Новые технологии)
The article presents the results of the study of the seasonal rhythm of growth and development of tea plants due to their response to environmental conditions (temperature factor and moisture supply factor). The relationship of the yield of breeding tea forms in the foothill zone of the Northwest Caucasus (the Republic of Adygea) with the winter hardiness of plants, with their characteristics of growth and formation of the crown (height, width and growth) during the growing season is examined, the dynamics of green leaf harvest for the leaf-harvesting period is analyzed and the quality of the collected flesh is assessed. Using the method of correlation analysis, it has been found that lengthening the period between the development of shoots of II and III orders is more dependent on the lack of moisture and does not depend on the sum of effective air temperatures in the previous period. In the course of two years of research, the greatest green leaf yield has been obtained from tAF-5 and AF-3 forms – 490.4 and 447.1 g, respectively, per plant.The best quality fleshes were formed in June, while the share of 2-sheet fleshes reached 85%. Based on the results, the studied breeding forms of tea are recommended for use in breeding local highly adaptive clone varieties.